Peran Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Keluarga - Yuliana Qurrota ‘Ayun; Agus Ahmad Safei; Ali Azis (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
The purpose of this study was to find out how the background was about PKH, how to implement PKH, and how the results of the existence of PKH on improving family welfare. This research method uses qualitative methods with a descriptive approach. The results of this study indicate that PKH appeared ini Ranjeng Village since 2014. The program aims to help the poor in terms of their economy, education and health. The implementation of its activities aims to improve the family’s economy so that all kinds of things they need can be fulfilled. The results of this PKH on improving the family’s economy can be said to be very helpful for every family that is less able, but because the program in Ranjeng Village does not yet exist such as training so that the community can develop the existing potential so the impact of the existence of this program the community becomes more dependent.